2021
DOI: 10.1097/mot.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

Are split liver grafts a suitable option in high-risk liver transplant recipients?

Abstract: Purpose of review To assess the outcomes of split liver transplantation (SLT) in adults and children and evaluate its role in high-risk recipients with a high model for end-stage liver disease (MELD) score, an urgent indication or requiring retransplantation. Recent findings Split liver grafts in general have equivalent long-term survival outcomes to whole grafts despite an increase in biliary complications. Recent success and technical advances have en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Elevated susceptibility to biliary complications stands as a significant risk factor in SLT [112,113,120]. The use of microvascular arterial reconstruction should be considered as one might in the case of pediatric living donor liver transplantation.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated susceptibility to biliary complications stands as a significant risk factor in SLT [112,113,120]. The use of microvascular arterial reconstruction should be considered as one might in the case of pediatric living donor liver transplantation.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Currently, most SLT outcomes remain uncertain, leading many transplant centers to adopt stringent donor selection criteria, typically favoring young, non-obese and hemodynamically stable donors. Similarly, recipient selection criteria, especially those necessitating urgent or re-transplantation, are rarely extended [120]. Research findings demonstrate that the 5-year survival rate of adult LT recipients (63% -69%) tends to be lower than that of whole LT [134][135][136][137].…”
Section: Patient and Graft Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 The post-operative graft and patient long-term survival rates for both LLL in paediatric recipients and eRL in adult recipients are generally comparable to the best results achievable with other techniques. 42,49,[57][58][59][60][61][62] However, there is a slightly higher rate of early post-operative complications and early mortality compared with WLT, although without statistical significance. 19,63,64 In current research, the majority of LLL splitting utilizes the in situ approach.…”
Section: Left Lateral Lobe Splittingmentioning
confidence: 99%
“…14 A longer CIT has also been reported as an independent factor affecting graft and patient survival rates. 20,30,49,60,79,96 A CIT of 10 h may be a critical number, and some studies have reported significant differences in outcomes when CIT is over 10 h compared with less than 10 h. 97 Besides, an appropriate GRWR is crucial to ensuring the safety and effectiveness of the transplant and has become a common criterion for evaluating whether certain liver grafts are suitable for transplantation. In LDLT, the recommended minimum GRWR is 0.6%, but in most cases, GRWR should be greater than 0.8%.…”
Section: The Factors Influencing the Outcome Of Sltmentioning
confidence: 99%